STUDI KOMPETENSI INTI DAERAH DI KABUPATEN BELU PROVINSI NUSA TENGGARA TIMUR - Thomas Ola Langoday (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
Core competence area is a collection of skills and technologies that enable an organi-zation can provide its own benefits for its customers. Thus, the high unique core com-petencies needed to achieve organizational objectives. The uniqueness of the organi-zation can make it difficult for competitors to imitate. By adopting the concept of onevillage and one product and concept SAKA SAKTI (one county / city of the corecompetencies) then to build the competitiveness of the region required the creation ofcore competencies for the area. This is necessary so that all resources and capabilitiesof the region focused on efforts to create a core competency. Based on the seven aspects of the value chain, namely raw materials, human resources, competitiveness,infrastructure, technology and information, social capital and institutional and secu-rity conditions, it is found that the commodity becomes a core competence area inBelu Regency is a patchouli plant and the results of various scent of patchoulioil. Patchouli plants available uniformly across the district and surrounding areas byabsorbing the workforce in large numbers, while patchouli oil industry with a distinc-tive aroma has penetrated the international market. Plants patchouli and patchoulioil industry (essential) to give high economic value added for those who manage it.Keywords: core competence areas, One Village One Product, SAKA SAKTI, atsiri oil(essential).